Sensitivity of the human back and buttocks: The missing link in comfort seat design. (January 2017) - Vink, Peter; Lips, Daan
Abstract: Purpose: The purpose of this study is to examine the differences in pressure sensitivity for areas of the human body in contact with the seat pan and backrest of a vehicle seat. These could provide a theoretical base for adapting the softness of the foam or the flexibility components used in seat design. Methods: Sensitivity was recorded at 32 points touching the seat pan and backrest by pushing a cylinder with a diameter of 20 mm into the seat until the participant reported that they were no longer comfortable. The force at which discomfort was reported was recorded using an advanced force gauge. Results and conclusions: The area of the body having contact with the front of the seat pan was more sensitive than the rest of those parts touching the seat pan. The area of the seat touching the shoulders was significantly more sensitive than the area in between the shoulders and lower down the back. Translating these findings directly into seat design should be done with care. Tests are still needed to confirm the assumed relationship between sensitivity and foam softness. Further information is also needed regarding the complete use of a seat, including analysis of vibrations while driving and comfort during ingress and egress. Highlights: differences in pressure sensitivity for areas of the human body in contact with the seat pan and backrest of a vehicle seat were determined. These could provide a theoretical base for adapting the softness of the foam or the flexibility components used in seat design. The area of the body having contact with the front of the seat pan was more sensitive than the rest of those parts touching the seat pan. The area of the seat touching the shoulders was significantly more sensitive than the area in between the shoulders and lower down the back. Translating these findings directly into seat design should be done with care. Tests are still needed to confirm the assumed relationship between sensitivity and foam softness. Further information is also needed regarding the complete use of a seat, including analysis of vibrations while driving and comfort during ingress and egress.